APPLICATION OF PROBLEM-BASED LEARNING MODEL ON MULTIPLICATION AND DIVISION MATERIAL TO IMPROVE STUDENT LEARNING OUTCOMES IN GRADE III SD NEGERI 4 BANDA ACEH - Soleha Puteri Mohamad Ramli; Syaila Annisa (Jurnal Ilmiah Teunuleh, 2022)
Based on observations, one of the problems in SD Negeri 4 Kota Banda Aceh is the low learning outcomes of students in mathematics subjects. The application of the Problem Based Learning model can provide a pleasant atmosphere for students in learning multiplication and division material. This study used the type of Classroom Action Research (PTK). The subjects of this study amounted to 23 students of grade III-B SD Negeri 4 Banda Aceh City, data collection techniques were carried out by observation, documentation, and learning outcomes tests. The technique of analyzing data from observations of student activities is with percentage descriptive statistics and individual student learning outcomes data. Based on the results of research in cycles I, II, and III obtained the following data: (1) the results of observations on student activities in learning observed for three cycles, increased in each cycle, namely: student activity in cycle I reached 82% of the good category, cycle II reached 84% of the good category, and cycle III reached 98% of the very good category. (2) the learning outcomes of students in multiplication and division material increased in cycle I of classical completeness criteria reaching 34% with an average value of 57.39, in cycle II classical completeness criteria of 69% with an average value of 71.37, while cycle III of classical completeness criteria 91% with an average value of 84.34. It was concluded that the Problem Based Learning learning model on multiplication and division material can improve the learning outcomes of grade III-B students of SD Negeri 4 Banda Aceh City.